(2,(3)×0,3+7,(1)×4,5)÷1,2
Răspunsuri la întrebare
Răspuns de
6
2,(3)=2 intregi 3/9 = 21/9 = 7/3
7,(1)=7 intregi 1/9 = 64/9
4,5=45/10=9/2
1,2=12/10=6/5
(7/3 · 1/3 + 64/9 · 9/2) · 5/6 =
(7/9 + 32) · 5/6 =
(7+32·9)/9 · 5/6 =
295/9 · 5/6 =
1475/54 =
27,3(148)
7,(1)=7 intregi 1/9 = 64/9
4,5=45/10=9/2
1,2=12/10=6/5
(7/3 · 1/3 + 64/9 · 9/2) · 5/6 =
(7/9 + 32) · 5/6 =
(7+32·9)/9 · 5/6 =
295/9 · 5/6 =
1475/54 =
27,3(148)
Alte întrebări interesante
Biologie,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă